(untitled) (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2026)
This article devoted to the implementation of English – language mediatexts, specifically news discourse, in the instructional process of teaching English to 11th grade students. The research primarily concentrates on enhancing learners’ lexical competence and pronunciation skills. The experimental design encompassed the administration of both pre – and post – assessment tasks to evaluate the effectiveness of the applied instructional strategy. The central objective was to assess whether systematic engagement with authentic materials facilitates the expansion of students’ active vocabulary. A quantitative approach was employed to analyze the assessment data collected at different stages of the study. The results revealed a measurable improvement in vocabulary acquisition, with participants demonstrating a one – level advancement in lexical proficiency following the intervention. These results indicate that the use and integration of media texts into the course of teaching English as a foreign language is effective and contributes to the improvement of vocabulary and pronunciation.